2017
DOI: 10.1650/condor-17-51.1
|View full text |Cite
|
Sign up to set email alerts
|

Nest site selection and nest survival of Greater Prairie-Chickens near a wind energy facility

Abstract: Rapid development of wind energy facilities in the Great Plains of North America has raised concerns regarding their potential negative impact on the nesting ecology of Greater Prairie-Chickens (Tympanuchus cupido pinnatus). We investigated the effects of a pre-existing, 36-turbine wind energy facility on nest site selection and nest survival of Greater Prairie-Chickens in the unfragmented grasslands of the Nebraska Sandhills, USA. In 2013 and 2014, we monitored 91 nests along a 24-km disturbance gradient lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
3
12
0
Order By: Relevance
“…Similar to our nest‐site selection results, we found no evidence of wind‐energy infrastructure affecting Columbian sharp‐tailed grouse nest survival. These results are similar to those of McNew et al () and Harrison et al () who found no influence of wind‐energy infrastructure on greater prairie‐chicken nest survival in Kansas and Nebraska, respectively. Both studies found nest survival was influenced by vegetation rather than wind‐energy infrastructure.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to our nest‐site selection results, we found no evidence of wind‐energy infrastructure affecting Columbian sharp‐tailed grouse nest survival. These results are similar to those of McNew et al () and Harrison et al () who found no influence of wind‐energy infrastructure on greater prairie‐chicken nest survival in Kansas and Nebraska, respectively. Both studies found nest survival was influenced by vegetation rather than wind‐energy infrastructure.…”
Section: Discussionsupporting
confidence: 91%
“…Our nest‐site selection results are similar to those of McNew et al () and Harrison et al () who reported no influence of wind‐energy development on nest‐site selection in greater prairie‐chickens. Similarly, LeBeau et al (2014, ) reported no influence of wind‐energy development on nest‐site selection in sage‐grouse.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For example, Winder and others reported adverse effects of a wind energy facility on female prairie-chicken space use (Winder et al 2014) and lek persistence (Winder et al 2015) in a grassland/agriculture system with almost three times (1.40 km/km²) higher road density as our study area (0.49 km/ km²). The presence of a wind facility and concomitant background noise in our relatively intact, unfragmented landscape appears to have fewer negative consequences because females do not appear to avoid nesting (Harrison et al 2017) or rearing broods in areas near the facility (Harrison 2015). Leks near and on wind facility property have been present after the facility's construction and still remain (B. Vodehnal, NE Game & Parks Commission, personal communication).…”
Section: Discussionmentioning
confidence: 99%